On the Enjoyment of Sad Music: Pleasurable Compassion Theory and the Role of Trait Empathy - Huron, David; Vuoskoski, Jonna K. (Frontiers in Psychology, 2020)
Drawing on recent empirical studies on the enjoyment of nominally sad music, a general theory of the pleasure of tragic or sad portrayals is presented. Not all listeners enjoy sad music. Multiple studies indicate that those individuals who enjoy sad music exhibit a particular pattern of empathic traits. These individuals score high on empathic concern (compassion) and high on imaginative absorption (fantasy), with only nominal personal distress (commiseration). Empirical studies are reviewed implicating compassion as a positively valenced affect. Accordingly, individuals who most enjoy sad musical portrayals experience a pleasurable prosocial affect (compassion), amplified by empathetic engagement (fantasy), while experiencing only nominal levels of unpleasant emotional contagion (commiseration). It is suggested that this pattern of trait empathy may apply more broadly, accounting for many other situations where spectators experience pleasure when exposed to tragic representations or portrayals.